ANALYSIS OF THE EFFECT OF PERCEPTION OF CONVENIENCE, TRANSPARENCY AND INSTITUTIONAL IMAGE ON INTEREST IN PAYING NON-CASH ZAKAT, INFAQ AND ALMS (ZIS) WITH TRUST AS A MODERATING VARIABLE (STUDY ON MUSLIM SOCIETY OF SALATIGA INDONESIA) - Irawati, Narendra (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
This study aims to examine the influence of perceived ease of use, transparency, and institutional image on the intention to pay Zakat, Infaq, and Shadaqah (ZIS) through non-cash methods among the Muslim community in Salatiga, Indonesia, with trust as a moderating variable. Despite the increasing adoption of digital payment systems like QRIS, ZIS collection by official zakat institutions (OPZ) remains suboptimal. This research is essential to identify key factors influencing digital ZIS payment interest and to provide strategic recommendations for OPZ in enhancing public trust. A systematic literature review of relevant national and international studies was conducted. The main outcome of this study is a conceptual framework that illustrates the relationship between perceived ease of use, transparency, and institutional image on the intention to pay non-cash ZIS, moderated by trust. This framework is expected to serve as a reference for developing more effective and adaptive digital zakat fundraising strategies. Keywords: Zakat, Infaq, and Shadaqah (ZIS) non-cash, perceived ease of use, transparency, institutional image, trust.